1936
DOI: 10.1017/s0022172400043849
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Preservation of Sera by Desiccation in the Frozen State Without the use of Refrigerants

Abstract: SummaryA simple process is described for the desiccation of antisera after freezing by rapid evaporation. Freezing has been brought about by the rapid evaporation which takes place in a high vacuum in the presence of P2O5. The violent frothing which takes place when serum is exposed to a high vacuum has been controlled by a preliminary evacuation of the serum in the absence of the drying agent.No special apparatus except an efficient high vacuum pump is necessary for this process.This process has been applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1939
1939
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Therefore we have thought that it would be of interest to publish results we obtained some years ago when testing the method for drying serum which has been described by Greaves & Adair (1936).…”
Section: Serummentioning
confidence: 99%
“…Therefore we have thought that it would be of interest to publish results we obtained some years ago when testing the method for drying serum which has been described by Greaves & Adair (1936).…”
Section: Serummentioning
confidence: 99%
“…The dry mass dissolves rapidly and completely in water, yielding a fluid which apparently does not differ in physical properties from the original solution (Adair & Robinson, 1931;Greaves & Adair, 1936;Elser, Thomas & Steffen, 1935;Flosdorf & Mudd, 1935, 1938. Proteins dried in this way may be preserved for long periods of time without undergoing deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…He found that by reducing the pressure slowly with a water pump, frothing could be controlled, till eventually a quiescent fluid resulted. Greaves & Adair (1936) made use of this observation for drying, from the frozen state, material in its final containers. They found that if vessels containing the protein solution were placed in a desiccator without any drying agent, and the pressure was reduced to about 12 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation